2019
DOI: 10.17843/rpmesp.2019.362.4076
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia y severidad de retinopatía diabética en pacientes con diabetes mellitus tipo 2 en el Instituto Regional de Oftalmología

Abstract: Para determinar la frecuencia y el grado de severidad de retinopatía diabética (RD) en pacientes con diabetes mellitus (DM) tipo 2 se realizó un estudio descriptivo transversal en 3239 pacientes del

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The 43 prevalence studies included 47 585 participants and their characteristics are shown in Table 1 . With respect to scientific production by country, eighteen studies were conducted in Brazil [ 30 , 32 , 33 , 35 37 , 39 42 , 44 , 50 , 54 , 58 , 59 , 65 67 ], twelve in Mexico [ 27 – 29 , 38 , 45 , 47 , 49 , 51 , 55 , 57 , 60 , 64 ], four in Cuba [ 31 , 34 , 43 , 48 ], two in Peru [ 46 , 61 ] two in Chile [ 63 , 69 ], and one in Argentina [ 68 ], Costa Rica [ 62 ], Ecuador [ 56 ], Puerto Rico [ 52 ], and Suriname [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 43 prevalence studies included 47 585 participants and their characteristics are shown in Table 1 . With respect to scientific production by country, eighteen studies were conducted in Brazil [ 30 , 32 , 33 , 35 37 , 39 42 , 44 , 50 , 54 , 58 , 59 , 65 67 ], twelve in Mexico [ 27 – 29 , 38 , 45 , 47 , 49 , 51 , 55 , 57 , 60 , 64 ], four in Cuba [ 31 , 34 , 43 , 48 ], two in Peru [ 46 , 61 ] two in Chile [ 63 , 69 ], and one in Argentina [ 68 ], Costa Rica [ 62 ], Ecuador [ 56 ], Puerto Rico [ 52 ], and Suriname [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the populations assessed, in twenty-four studies the participants were assessed in the hospital [ 29 , 32 35 , 37 41 , 44 – 46 , 49 – 52 , 56 – 58 , 62 , 65 , 67 , 68 ], ten in the community [ 18 , 19 , 21 , 33 , 34 , 38 , 44 , 46 , 50 , 51 ], and nine in primary care [ 31 , 36 , 48 , 54 , 61 , 63 , 64 , 66 , 69 ]. For the type of DM, eight studies assessed T1DM [ 32 , 34 , 35 , 39 , 40 , 44 , 50 , 58 ], eighteen T2DM [ 27 , 33 , 37 , 41 , 42 , 45 , 46 , 48 , 49 , 51 , 54 –…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graciela Santos y col. (13) estiman la prevalencia de microcefalia, información relevante dada la carencia de estudios basales, lo cual no permite determinar el impacto de algunas enfermedades emergentes como fue en su momento fue el Zika. También es interesante, el artículo Rosa Adrianzén y col. (14) sobre la necesidad de hacer una evaluación integral de los pacientes con diabetes mellitus desde su diagnóstico para abordar oportunamente complicaciones como la retinopatía diabética.…”
Section: Editorialunclassified